Clinical Controversy Surrounding the Differential Diagnosis of Branchiogenic Carcinoma - Karatzanis, Alexander; Mylopotamitaki, Kleanthi; Lagoudaki, Eleni; Prokopakis, Emmanuel; Agelaki, Sofia (Case Reports in Otolaryngology, 2022)
Clinical evaluation, differential diagnosis, and management of a neck mass constitute commonly encountered problems for the head and neck surgeon. An asymptomatic neck mass in adults may be the only clinical sign of head and neck cancer. A 50-year-old female patient presented with a painless, slowly enlarging, left lateral neck lump. Ultrasonography described a possible lymph node with cystic degeneration, and fine needle aspiration biopsy only detected atypical cells of squamous epithelium. An open biopsy under general anesthesia was performed. Histopathological findings suggested the diagnosis of lymph node infiltration by squamous cell carcinoma of an unknown primary site, but differential diagnosis also included branchiogenic carcinoma arising in a branchial cleft cyst. A diagnostic algorithm for metastatic squamous cell carcinoma of an unknown primary site was followed, including positron emission tomography with computed tomography. The patient underwent panendoscopy and bilateral tonsillectomy, and an ipsilateral p16 positive tonsillar squamous cell carcinoma was detected. Further appropriate management followed. The existence of true branchiogenic carcinoma is controversial. When such a diagnosis is contemplated, every effort should be made to detect a possible primary site. Branchiogenic carcinoma, if exists at all, remains a diagnosis of exclusion.